A Observação Participante na Investigação em Turismo - Marujo, Noémi (2012)
In recent decades, tourism has undergone rapid changes in the focus of research. These changes are especially related to two issues: how to investigate and what to investigate. In tourism, as in all other areas, the investigator must choose the method and research techniques that he considers most appropriate for their theme study. This paper analyzes the importance of the technique 'participant observation' for tourism studies. The author used as methodology bibliographic review and used a few practical studies to illustrate the role of this method of data collection in tourism research